2011
DOI: 10.1093/bja/aer034
|View full text |Cite
|
Sign up to set email alerts
|

Continuous care and empathic anaesthesiologist attitude in the preoperative period: impact on patient anxiety and satisfaction

Abstract: The 'one patient, one anaesthesiologist' model, in addition to ensuring sufficient time for open discussion and questions at the preoperative visit, improved patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 30 publications
1
61
0
7
Order By: Relevance
“…Being there for the patient throughout the operation ensured reassurance. These findings are supported by Soltner et al [29], who found that patients being cared for by just one emphatic anesthesiologist were more satisfied and rated quality of care higher. Emphatic behavior was also related to reduced levels of anxiety.…”
Section: Discussionsupporting
confidence: 55%
“…Being there for the patient throughout the operation ensured reassurance. These findings are supported by Soltner et al [29], who found that patients being cared for by just one emphatic anesthesiologist were more satisfied and rated quality of care higher. Emphatic behavior was also related to reduced levels of anxiety.…”
Section: Discussionsupporting
confidence: 55%
“…Although some studies report that physiological and music intervention is effective in reducing anxiety levels,5,6,7,8 few studies have examined the effects of physiological and music intervention on perioperative safety in elderly patients. For example, psychological intervention and direct communication with patients by anesthetists and nurses before surgery was found to effectively reduce patient anxiety and improve patient satisfaction 7.…”
Section: Introductionmentioning
confidence: 99%
“…Very important is the empathic attitude of an anesthesiologist to a patient who wants to feel safe and needs psychological support [8]. Provision in the preoperative period to the patient of exhaustive information about anesthesia, discussion with the patient of the choice of the method are the most important factors affecting the satisfaction with anesthesia.…”
Section: The Results and Discussionmentioning
confidence: 99%
“…Detailed information on methods for assessing satisfaction can be found in the article Barnett et al [6]. Highquality studies of patient satisfaction with anesthesia are rare [7].Very important is the empathic attitude of an anesthesiologist to a patient who wants to feel safe and needs psychological support [8]. Provision in the preoperative period to the patient of exhaustive information about anesthesia, discussion with the patient of the choice of the method are the most important factors affecting the satisfaction with anesthesia.…”
mentioning
confidence: 99%